2017
DOI: 10.1016/j.neulet.2017.05.056
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-associated tau contributes to intra-dendritic trafficking of AMPA receptors in multiple ways

Abstract: Microtubule-associated protein tau has crucial roles not only in the formation of some neurodegenerative disorders but also in normal synaptic functions, although its contributions to these are still unclear. Here, to reveal the influence of tau deletion on trafficking of synaptic receptors, we investigated the distribution of GluA2-containing AMPA-type glutamate receptors (AMPARs) within neuronal dendrites in wild-type and tau-deficient neurons using biochemical and laser-confocal imaging techniques. Under ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
4
13
0
Order By: Relevance
“…Given that the extended absence of functional glutamatergic receptors can threaten spine stability, disruptions in the targeting and/or anchoring of these receptors may also contribute to spine loss (Cingolani & Goda, 2008;Matus, 2000). It is feasible that pS214-tau participates in glutamate receptor localization to the synapse here, as reported by others, a possibility worth exploring in future work (L. M. Ittner et al, 2010;Lau et al, 2016;Miller et al, 2014;Mondragon-Rodriguez et al, 2012;Suzuki & Kimura, 2017).…”
Section: Synaptic Ps214-tau and Cognitive Statusmentioning
confidence: 75%
“…Given that the extended absence of functional glutamatergic receptors can threaten spine stability, disruptions in the targeting and/or anchoring of these receptors may also contribute to spine loss (Cingolani & Goda, 2008;Matus, 2000). It is feasible that pS214-tau participates in glutamate receptor localization to the synapse here, as reported by others, a possibility worth exploring in future work (L. M. Ittner et al, 2010;Lau et al, 2016;Miller et al, 2014;Mondragon-Rodriguez et al, 2012;Suzuki & Kimura, 2017).…”
Section: Synaptic Ps214-tau and Cognitive Statusmentioning
confidence: 75%
“…summarises how the effects of Tau on electrophysiological measurements have a large degree of variability depending upon the methods applied. The most consistent finding appears to be that exogenous oligomeric Tau impairs LTP, with monomeric Tau having no effect [123,251,352,360,434]. Fá et al [123] showed that a 20 min treatment of CA3-CA1 hippocampal neurons with oligomeric 4R2N Tau before induction of LTP caused a marked reduction in LTP expression without affecting basal synaptic transmission.…”
Section: Relating Tau Pathology To Models Of Memory Impairmentmentioning
confidence: 98%
“…Tau is not known to directly bind PICK1, GluA2, though there is an NMDA-dependent interaction of this complex with phospho-Tau [370]. These proteins are therefore added to the figure in order to highlight specific pathways that have been previously mentioned in the literature [434] the earliest stages of CME to occur [275,277]. Transferrin receptors are therefore also important for activitydependent AMPAR internalisation that is dependent on CME and required for LTD as they recruit AP2 (adaptor protein 2).…”
Section: Transferrin Ap2 and Dynamin-1; Possible Role Of Tau In Early Stages Of Cmementioning
confidence: 99%
See 1 more Smart Citation
“…A proper balance in the number of phosphorylated and dephosphorylated residues of Tau favors its classical physiological role in neurite outgrowth, axonal transport and microtubule dynamics. In addition, due to its scaffolding property, Tau can bind to a variety of proteins, therefore impacting multiple physiological functions (Meier et al, 2015; Suzuki and Kimura, 2017; Zhou et al, 2017; Stefanoska et al, 2018). Many of these interactions still remain to be uncovered.…”
Section: Introductionmentioning
confidence: 99%